2013
DOI: 10.3389/fonc.2013.00314
|View full text |Cite
|
Sign up to set email alerts
|

Design of Optimized Hypoxia-Activated Prodrugs Using Pharmacokinetic/Pharmacodynamic Modeling

Abstract: Hypoxia contributes to resistance of tumors to some cytotoxic drugs and to radiotherapy, but can in principle be exploited with hypoxia-activated prodrugs (HAP). HAP in clinical development fall into two broad groups. Class I HAP (like the benzotriazine N-oxides tirapazamine and SN30000), are activated under relatively mild hypoxia. In contrast, Class II HAP (such as the nitro compounds PR-104A or TH-302) are maximally activated only under extreme hypoxia, but their active metabolites (effectors) diffuse to ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 85 publications
0
42
0
Order By: Relevance
“…Three-dimensional simulations were performed in a digitized microvascular network previously obtained from a mapped FaDu window chamber xenograft [32] to represent tumor tissue and a mapped rat cremaster muscle microvascular network [33] to represent well-organized normal tissue as previously described for anti-cancer prodrugs [34]. The 3D reaction diffusion equations are solved for oxygen and ascorbate using a Green's function approach [27,33], which calculates the oxygen and intracellular and extracellular ascorbate concentrations at each tissue point and includes extraction from the blood vessels.…”
Section: Virtual Histology Simulations In Tumor and Normal Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional simulations were performed in a digitized microvascular network previously obtained from a mapped FaDu window chamber xenograft [32] to represent tumor tissue and a mapped rat cremaster muscle microvascular network [33] to represent well-organized normal tissue as previously described for anti-cancer prodrugs [34]. The 3D reaction diffusion equations are solved for oxygen and ascorbate using a Green's function approach [27,33], which calculates the oxygen and intracellular and extracellular ascorbate concentrations at each tissue point and includes extraction from the blood vessels.…”
Section: Virtual Histology Simulations In Tumor and Normal Tissuementioning
confidence: 99%
“…Mapped, digitized microvessel networks of FaDu xenografts from rat window chambers [32] or rat cremaster muscle tissue [33], previously used to simulate drug distribution [34], were used with the ascorbate diffusion model. The vascular network of normal tissue, which has a maximum intervessel distance of 50 μm, is clearly more organized and functional compared to the FaDu tumor tissue vasculature (Fig.…”
Section: Virtual Histology Heat Maps Of Ascorbate Diffusion Through Tmentioning
confidence: 99%
“…Mathematical models explored how to effectively use HAPs. Foehrenbacher et al [108] used a Green's function approach to calculate tumour response to this treatment and the 3D spatial and longitudinal gradients of oxygen and drug concentrations. The authors showed that, to increase HAPs' antitumour activity, the rates of effector stability and pro-drug activation should be optimized.…”
Section: Mathematical Models Of Anti-cancer Therapiesmentioning
confidence: 99%
“…Multiple HAPs have been evaluated for their clinical potential, both as monotherapies and as part of combination therapies [12,8]. Class I HAPs are activated in moderately hypoxic environments whilst Class II HAPs require more severe hypoxia to undergo the HAP to AHAP bioreduction [23]. One such Class II HAP is evofosfamide, or TH-302, which has been tested in clinical Phase I-III trials [12,1].…”
Section: Introductionmentioning
confidence: 99%
“…Foehrenbacher et al [30] have deployed a Green's function method, in customised form, and pharmacokinetic/pharmacodynamic (PK/PD) modelling to quantify anticancer bystander effects elicited by the HAP PR-104 in a simulated, three-dimensional tumour comprising a microvascular network. Another concurrent article used similar mathematical concepts to compare Class I HAPs to Class II HAPs and, furthermore, to determine optimal properties for Class II HAPs [23]. Lindsay et al [31] developed a stochastic model to study monotherapies and combination therapies involving HAPs, specifically TH-302, and erlotinib.…”
Section: Introductionmentioning
confidence: 99%